GANGGUAN PENDENGARAN AKIBAT BISING PENGGUNAAN HEADPHONE/EARPHONE: Noise Induce Hearing Loss Due to Usage of Headphone/Earphone - Hendradewi, Sarwastuti; Setiamika, Made; Sudrajad, Hadi; Kandhi, Putu Wijaya; Primadewi, Novi; Pratiwi, Dewi; Yusuf, Destar Aditya (Universitas Muhamamdiyah Surakarta, 2023)
ABSTRAK Gangguan pendengaran akibat bising (GPAB) sering dijumpai pada usia pelajar. Adanya kemajuan alat elektronik beserta kemudahan dalam mengakses internet dan sosial media menyebabkan pelajar sering menggunakan personal listening device seperti headphone/earphone untuk mengakses informasi dari piranti elektronik tersebut. Identifikasi gangguan pendengaran secara dini dan intervensi yang sesuai terbukti dapat mencegah konsekuensi tersebut. Tujuan diselenggarakan kegiatan ini adalah untuk memberikan edukasi gangguan pendengaran akibat bising (GPAB) dan untuk mengetahui sejak dini kondisi telinga dan pendengaran pelajar dan memberikan intervensi dan tatalaksana sesuai kebutuhan. Metode dalam kegiatan ini direncanakan dilakukan melalui tahapan - tahapan sesuai dengan petunjuk pengendalian HIRARC (hazard identification, risk assessment, and risk control). Hasil kegiatan ini didapatkan pendengaran 147 siswa dalam batas normal, 31 siswa terdapat serumen, 7 siswa Otitis Eksterna, 3 siswa OMSK, dan 4 orang siswa dicurigai menderita gangguan pendengaran akibat bising. Siswa yang dicurigai menderita gangguan pendengaran akibat bising dianjurkan ke RSUD Dr. Moewardi Surakarta untuk dilakukan pemeriksaan dan tatalaksana lebih lanjut. ABSTRACT Noise induce hearing loss (NIHL) is often found in students. The advancement of electronic devices along with the ease of accessing the internet and social media has caused students to often use personal listening devices such as headphones/earphones to access information from these electronic devices. Early identification of hearing loss and appropriate intervention have been shown to prevent such consequences. The purpose of this activity was to educate noise induce hearing loss (NIHL) and to know early on the ear and hearing condition of students and provided intervention and management as needed. The method in this activity was planned to be carried out through stages in accordance with the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) control instructions. The results of this activity obtained the hearing of 147 students within normal limits, 31 students with cerumen, 7 Otitis Externa students, 3 OMSK students, and 4 students with suspect of noise induce hearing loss. Students who were suspected of suffering from hearing loss due to noise were recommended to Dr. Moewardi Surakarta Hospital for further examination and management.